The Effect of Imegery Training on Increasing Shooting Accuracy in the 10 m Air Rifle Women's Class Before Porprov XI in 2022 - Soemardiawan, Soemardiawan; Nurdin, Nurdin; Anggraeni, Fitri (JUPE : Jurnal Pendidikan Mandala, 2023)
The research problem is the low ability to shoot air rifles in Class 10 m Air Rifle Women athletes before PORPROV XI 2022, due to the still weak accuracy of the players. This is evident from the various tournaments that have taken part, very rarely athletes are able to shoot on target. Mental imagery is one of the mental exercises that really has an influence on improving performance, especially in shooting. The purpose of this study was to determine the effect of imagery training on increasing the accuracy of the 10 m Air Rifle Women Class before PORPROV XI 2022. The research design used was experimental one pre-test-post-test group, and the type of research is using experimental research. The research sample consisted of 9 athletes shooting the PERBAKIN NTB air rifle. The research instrument used was shooting 60 shots for 75 minutes. Based on data processing and analysis, the increase in the results of the initial training test was 73.33%. So the researchers concluded that: "There is an effect of imagery training on increasing the accuracy of the 10 m Class Air Rifle Women's shot before PORPROV XI 2022" meaning that there is a significant (real) effect of mental imagery training on the shooting skills of athletes shooting air rifles.